2021
DOI: 10.1002/cbdv.202100706
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Phytochemical Composition, Antioxidant and Enzyme Inhibition Potential of Polygonum Plebeium R.Br: A Comprehensive Approach to Disclose New Nutraceutical and Functional Food Ingredients

Abstract: The present work describes medicinal potential and secondary metabolic picture of the methanol extract (PP-M) of Polygonum plebeium R.Br. and its fractions; hexane (PP-H), ethyl acetate (PP-E) and water (PP-W). In total bioactive component estimation, highest contents of phenolic (89.38 � 0.27 mgGAE/g extract) and flavonoid (51.21 � 0.43 mgQE/g extract) were observed in PP-E, and the same fraction exhibited the highest antioxidant potential in DPPH (324.80 � 4.09 mgTE/g extract), ABTS (563.18 � 11.39 mgTE/g ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Interestingly, all the fractions exhibited nearly equal potential with the polar fractions CAÀ B (37.35 � 0.53 mg KAE/g extract) and CAÀ E (36.22 � 1.01 mg KAE/g extract) displayed slightly high- er activities, which revealed that not only phenolic compounds but also other polar metabolites probably including glycosides may also impart to the inhibition process. Literature reports supported our findings where a mix trend is observed for anti-tyrosinase activity of plant extracts [14,47,48] however, these results disclosed the anti-browning and skin whitening capacity of C. arvensis.…”
Section: Tyrosinase Inhibitory Activitiessupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, all the fractions exhibited nearly equal potential with the polar fractions CAÀ B (37.35 � 0.53 mg KAE/g extract) and CAÀ E (36.22 � 1.01 mg KAE/g extract) displayed slightly high- er activities, which revealed that not only phenolic compounds but also other polar metabolites probably including glycosides may also impart to the inhibition process. Literature reports supported our findings where a mix trend is observed for anti-tyrosinase activity of plant extracts [14,47,48] however, these results disclosed the anti-browning and skin whitening capacity of C. arvensis.…”
Section: Tyrosinase Inhibitory Activitiessupporting
confidence: 89%
“…[13] The results are expressed in terms of milligrams of gallic acid equivalent per gram of the extract (mg GAE/g extract). Total flavonoid contents were determined using the aluminium chloride colorimetric method [14] with the results expressed as mg rutin equivalent per gram of the extract (mg RE/g extract). UHPLC/MS analysis was used to assess the secondary metabolites composition of the methanol extract (CAÀ M) in positive ionization mode.…”
Section: Estimation Of Total Phenolic and Flavonoid Contents And Uhpl...mentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant potential of P. candollei was tested by six different methods, which include DPPH, ABTS, FRAP, CUPRAC, and TAC (phosphomolybdenum assay) by previously described methods [131,132]. The results were expressed as equivalent to Trolox, whereas the metal-chelating property was expressed as equivalent to ethylene diamine tetraacetic acid (EDTA), and all the readings were taken in triplicates.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…The enzyme-inhibitory potential of all fractions was tested against tyrosinase, αamylase, and α-glucosidase by using the methods reported in the literature [132]. Tyrosinase inhibition was measured as kojic acid equivalent, and inhibition of enzymes, responsible for hyperglycemia (α-amylase and α-glucosidase) was observed by acarbose equivalent potential of the extract, and its fractions and three readings were taken for each assay.…”
Section: In Vitro Enzyme Inhibition Activitiesmentioning
confidence: 99%